Analisis Pemodelan Rasch: Skala Tatapikir Kedamaian Siswa - Dadang Sudrajat; Sunaryo Kartadinata; Uman Suherman (Universitas Mathla'ul Anwar Banten, 2019)
RASCH MODELING ANALYSIS: SCALE OF STUDENT PEACE OF MINDSET. This study aims to develop a scale of early detection of peace thinking in the context of standardized Indonesian culture. The study using a descriptive method for 1118 students from several public high schools in Bandung through Rasch modeling analysis. It is reported that all items are correctly perceived by students, with excellent internal consistency and good unidimensionality. The implication shows that there is still a need for further scale research based on a more diverse level of education units, including among santri (student) in Islamic boarding schools (pesantren) so that the results are conclusive and comprehensive, with urban or rural backgrounds. This research explains a dynamic, progress, and a second stage that is good in developing TNT's scale into an ethnically diverse Indonesian context.